2016
DOI: 10.1002/jrs.5060
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bond network relaxation resolved by alcohol hydration (methanol, ethanol, and glycerol)

Abstract: Although the alcohol–water mixtures are ubiquitously important to beverage and pharmacy industries, it remains yet puzzling how the alcohols interact with water molecules and how the alcohol molecules functionalize the hydrogen bond network of liquid water and body fluid. We show spectrometrically that alcohol hydration softens both the H–O bond and the O:H nonbond through hydrogen bond cooperative relaxation and associated charge polarization. Observations suggested that each of the dangling hydroxide group :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The results show the interfacial thickness to be significantly larger than the estimated 5.5 Å used previously by Li et al [14] In the literature, it has been shown that both hydroxyl and methyl groups of ethanol have distinctive hydration layers [38] and can disrupt the network of hydrogen bonds at the solution's surface. [39] As a result, the effective interfacial layer should include the hydration shells of the alcohol molecules, [40] making it larger than a lone ethanol molecule.…”
Section: Interfacial Thicknessmentioning
confidence: 50%
“…The results show the interfacial thickness to be significantly larger than the estimated 5.5 Å used previously by Li et al [14] In the literature, it has been shown that both hydroxyl and methyl groups of ethanol have distinctive hydration layers [38] and can disrupt the network of hydrogen bonds at the solution's surface. [39] As a result, the effective interfacial layer should include the hydration shells of the alcohol molecules, [40] making it larger than a lone ethanol molecule.…”
Section: Interfacial Thicknessmentioning
confidence: 50%
“…As a result of water solubility in alcohols reduced with increasing temperature, the alcohol regenerates in the acidic medium and forms CH 3 NH 3 + (reaction ). For the growth reactions in 1‐butanol and 2‐butanol, the perovskite growth is performed at room temperature due to their relatively limited solubility of water with the effect of their increased hydrophobic chain length …”
Section: Resultsmentioning
confidence: 99%
“…In order to minimize hydrated complexes for device fabrication, the perovskite films are rinsed with 2-propanol. [43] The energy change for the formation of PbI 3 − from the dissociation of PbI 4 2− is −0.02 eV (reaction (5)) promotes PbI 3 − to obtain in the alcohol medium. As a result of water solubility in alcohols reduced with increasing temperature, the alcohol regenerates in the acidic medium and forms CH 3 NH 3 + (reaction (11)).…”
Section: Growth Mechanismmentioning
confidence: 99%
“…Although the alcohol–water mixtures are ubiquitously important to the beverage and pharmacy industries, it remains yet puzzling how the alcohols interact with water molecules and how the alcohol molecules functionalize the hydrogen bond network of liquid water and body fluid. The authors show spectrometrically that alcohol hydration softens both the HO bond and the O:H nonbond through hydrogen bond cooperative relaxation and associated charge polarization . Hu et al carried out a Raman investigation on pure D 2 O/H 2 O from 303 to 573 K with interpretation and implications for the structure of water.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%